Oral Mucosal Lesions in Patient With Bullous Pemphigoid - A Rare Case and Literature Review - E, Deliverska; J, Kirilova; L, Stefanov (Journal of Diseases, 2018)
Bullous pemphigoid /BP/ is a chronic blistering disorder that can affect oral mucosa very rarely. This autoimmune disease typically has a gradual onset and a chronic progressive course with exacerbations and remissions. Against components located in the epithelial basement membrane are formed autoantibodies. It is important to perform an incisional biopsy to establish a definitive diagnosis. Direct immunofluorescent findings are identical in BMMP and BP. Indirect immunofluorescence shows circulating IgG antibodies against the components of basement membrane in the majority of cases with BP but very rarely in patients with BMMP. There is no correlation between antibody titer and disease severity in BP. The aim is to present a very rare case of bullous pemphygoid of oral mucosa histologically proved with immunostaining. We present a patient with clinically identified oral lesion - bullae with clear fluid content in buccal mucosa of maxilla. After the rupture of bullae it left painful, superficial, ulcerated areas of oral mucosa. Hystopathological examination revealed subepithelial blister formation with clean separation of the full thickness of the epithelium from the underlying connective tissue layer. Direct immunofluorescence revealed a continuous linear band of immunoreactants at the basement membrane area. This immune deposit consist mainly IgG and C3, localized in the basement membrane. Conclusion: The treatment depends on the severity of the disease, tendency of progression and the affected areas. Therefore the clinicians should thoroughly examine all mucosal sites in order to make a proper diagnosis. The chronically characteristic of this autoimmune disease can lead to significant morbidity to patients. The adverse effects from long-term use of corticosteroids and immunosuppressives agents can also contribute to morbidity.